TEKNIK PEMBUATAN FIXED FIXED BRIDGE PFM PADA KEHILANGAN GIGI 41, 31, DAN 32, PADA RESORPSI ALVEOLAR DAN RONGAK KECIL - Alga Meisha Purwanto; Winda kusumawardani; Sri Redjeki Indiani; Sianiwati Goenharto; Anisa Nur Halimah; Narta Nikita Indiani; Widya Ulfa (Dentin, 2025)
ABSTRACT Background: Tooth loss is often accompanied by alveolar bone resorption and reduced edentulous space, leading to changes in bone morphology and imbalance of the dental arch. Alveolar resorption refers to the reduction in bone volume and height in the area of missing teeth, while reduced edentulous space is defined as a narrower space than the ideal dimension for prosthetic replacement. One method to restore function and aesthetics in cases of tooth loss is the fabrication of a fixed-fixed bridgeusing Porcelain Fused to Metal (PFM). Objective: To describe the fabrication technique of a fixed-fixed PFM bridge for the replacement of missing teeth 41, 31, and 32 associated with alveolar bone resorption and reduced edentulous space. Case: The working model presented missing teeth 41, 31, and 32 accompanied by alveolar bone resorption and reduced edentulous space, for which a fixed-fixed PFM bridge was planned. Conclusion: The fabrication of a fixed-fixed Porcelain Fused to Metal bridge for the replacement of teeth 41, 31, and 32 with alveolar bone resorption and reduced edentulous space begins with receiving the working model, followed by wax-up of the coping to cover the resorbed area. The line angles are slightly shifted toward the proximal surfaces to create the visual impression of wider teeth. This is followed by metal coping finishing and subsequent application of slurry, opaque, dentin, enamel, translucent, and pink ceramic at the cervical pontic area. The process is completed with staining and glazing to enhance porcelain color and luster, and final polishing of the collar to achieve a smooth and esthetic result.Keywords : alveolar bone resorption, fixed-fixed bridge, narrow space, pink ceramic, porcelain fused to metal (PFM) ABSTRAK  Latar Belakang: Kehilangan gigi sering disertai resorpsi tulang alveolar dan rongak kecil yang menyebabkan perubahan bentuk tulang dan ketidakseimbangan lengkung rahang. Resorpsi alveolar adalah penurunan volume dan tinggi tulang di area gigi yang hilang. Rongak kecil adalah jarak edentulous yang lebih sempit daripada ukuran ideal. Salah satu cara mengembalikan fungsi dan estetika pada gigi yang hilang adalah dengan pembuatan gigi tiruan jembatan fixed-fixed bridge dengan bahan Porcelain Fused to Metal (PFM). Tujuan: Untuk menjelaskan teknik pembuatan teknik pembuatan gigi tiruan jembatan PFM pada kehilangan gigi 41, 31, dan 32 yang disertai resorpsi alveolar dan rongak kecil. Kasus: Pada model kerja terdapat kehilangan gigi 41, 31, dan 32 disertai resorpsi tulang alveolar dan rongak kecil yang akan dibuatkan fixed-fixed bridge PFM. Kesimpulan: Tahapan pembuatan gigi tiruan jembatan fixed fixed bridge dengan bahan Porcelain Fused to Metal pada kehilangan gigi 41, 31, dan 32 yang mengalami resorpsi alveolar dan rongak kecil diawali dengan penerimaan model kerja, pembuatan wax-up coping menutupi area yang mengalami resorpsi dan line angle dibuat sedikit ke arah proksimal guna memberikan kesan gigi lebih lebar secara visual, finishing pada koping logam, kemudian dilanjutkan dengan pengaplikasian slurry, opaque, dentin, enamel, translucent, dan pink ceramic pada area servikal pontik. Setelah itu dilakukan proses staining dan glazing untuk menyempurnakan warna dan kilap porselen, lalu tahap akhir berupa pemolesan pada collar hingga diperoleh hasil yang halus dan estetis. Kata kunci : fixed-fixed bridge, pink ceramic, porcelain fused to metal (PFM), resorpsi tulang alveolar, rongak kecil